Allocation of decision rights between the parent company and its subsidiaries - LIU, Yuanyuan (Institutional Knowledge at Singapore Management University, 2018)
This article examines the determinants of allocation of decision rights between the parent company and its subsidiaries, and the economic consequence of suboptimal power structure. Based on China’s unique double disclosure for the parent company and the whole group, we construct a decentralization index to measure how decision rights are allocated within the group companies. We find a more decentralized (centralized) power structure for the groups with more uncertain (certain) external environment and with poorer (better) internal information quality. We also show that the groups with suboptimal power structure have weaker future performance.